2011
DOI: 10.1093/abbs/gmr042
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B induces rapid depletion of the G-actin pool through reactive oxygen species-dependent actin aggregation in melanoma cells

Abstract: Cucurbitacin B (CuB), a triterpenoid compound isolated from Cucurbitaceae plants, has been reported as a promising anti-cancer agent, yet its action mechanism is still controversial. In this study, we explored the potential mechanism of CuB in murine B16F10 melanoma cells. Anti-proliferation and anti-invasion effects were assessed in cultured cells, and in vivo anti-tumor activity was evaluated in a murine subcutaneous melanoma model. Flow cytometry was adopted to analyze cell cycle distribution and reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 34 publications
6
53
0
Order By: Relevance
“…Notably, activation of RhoA signaling and stress fiber formation by cucurbitacin I was dependent upon the generation of intracellular ROS. Recent studies in a number of cancer cellular models showed that cucurbitacins I and B induce the production of ROS (Yasuda et al, 2010;Zhang et al, 2011Zhang et al, , 2012b), as we observed in breast cancer cells. We found that the specific ROS mitochondrial antioxidant Mito-TEMPO prevented the effect of cucurbitacin I on Rac inhibition, arguing that mitochondrial-derived ROS have a prominent role in this effect.…”
Section: Discussionsupporting
confidence: 78%
“…Notably, activation of RhoA signaling and stress fiber formation by cucurbitacin I was dependent upon the generation of intracellular ROS. Recent studies in a number of cancer cellular models showed that cucurbitacins I and B induce the production of ROS (Yasuda et al, 2010;Zhang et al, 2011Zhang et al, , 2012b), as we observed in breast cancer cells. We found that the specific ROS mitochondrial antioxidant Mito-TEMPO prevented the effect of cucurbitacin I on Rac inhibition, arguing that mitochondrial-derived ROS have a prominent role in this effect.…”
Section: Discussionsupporting
confidence: 78%
“…Analysis of the cell cycle was performed as described previously [22]. In brief, the cells were fixed and stained with phosphate-buffered saline (PBS) containing 50 µg/ml propidium iodide and 30 µg/ml of RNase A. DNA content data were acquired using CELL Quest software on a flow cytometer (FACSCalibur; Becton Dickinson).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, several studies have reported that CuB activates the phosphorylation of Erk1/2 or has no significant effect on them [19,20,21], whereas others have indicated that CuB inhibits Erk1/2 phosphorylation [5,12]. Previous studies have also shown that CuB induces cell cycle arrest at the G 2 /M phase and formation of multinuclear cells in tumor cells [5,6,7,12,13,14,17], probably due to the disruption of the actin cytoskeleton [4,5,6,14,22]. Therefore, further investigations on the action mechanism of CuB are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been growing interest in CuB-mediated anticancer activities, mainly mediated through induction of G 2 -M phase cell-cycle arrest, inhibition of the JAK/STAT pathway, and induction of apoptosis (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%